History of Intellectual Culture 1/2022 Participatory Knowledge - Lerg, Charlotte A.; Östling, Johan; Weiß, Jana (History of Intellectual Culture, 2022)
The theme of the first issue of the yearbook HIC deals with "Participatory Knowledge". It will target the various ways knowledge is rooted in society through the participation of individuals and groups. Topics may include different kinds of knowledge harnessed within or through communities, modes of producing, circulating, and recording knowledge content.